Non-linear association of efficiency of practice of adult elite athletes with their youth multi-sport practice - Barth, M.; Güllich, A. (Journal of Sports Sciences, 2021)
We explored associations of elite athletes` multi-year efficiency of practice and improvement of performance with their current and earlier participation patterns. Participants were 80 adult German track-and-field national-squad athletes. Performance improvement was measured as development of athletes` highest track-and-field championship level and placing from 19 to 25 years (t1-t2). Practice efficiency was defined as performance improvement per amount of coach-led athletics practice from t1 to t2. Participation variables included amounts of coach-led practice and peer-led play in athletics and other sports through t1 and t1-t2. Analyses involved an advanced machine learning procedure, XGBoost, allowing non-linear, multivariate exploration. We computed two models, one for performance improvement ("good" discriminative performance, AUC = 0.82) and one for practice efficiency ("fair", AUC = 0.73). Four central findings emerged: 1. Childhood/adolescent coach-led multi-sport practice was a critical discriminator of adult practice efficiency and performance improvement. 2. Associations were non-linear, displaying a saturation pattern. 3. The likelihood of achieving high adult practice efficiency was greatest when combining ~1,000-2,500 track-and-field practice hours until t1 with ~1,250 other-sports practice hours until t1. 4. Peer-led engagement in any sport had negligible effects. Childhood/adolescent multi-sport coach-led practice apparently facilitated long-term sustainability of athletes` development of adult practice efficiency and performance improvement in athletics.